Prototype development of optimum irregular milling tools for chatter supression in machining automotive product - Yusoff, A. R.; Yahya, Nafrizuan Mat; Hamedon, Zamzuri B.; Yusoff, Wan Azhar; Shaharudin, Mohd Ali Hanafiah; Osman Zahid, Muhammed Nafis
Machining processes with high productivity cause tool wear and materials defects even damage machine spindle and limited by self-excited vibration or chatter. Chatter is a kind of self-excited vibration common in machining operations when increasing material removal rate. This is undesirable because it results in premature tool wear, poor surface finish on the machined component and the possibility of serious damage to the machine itself. In this project, optimum tool geometry of variable helix and variable pitch based on chatter stability lobe diagram created from modal analysis and cutting force coefficient determination developed. This prototype optimum irregular tools OF 12, 16 and 20 mm geometries achieved 20 percent more productivity than commercial regular milling tool in suppressing chatter.